Analyzing soil nutrient balances on small‐scale farms in the mid‐hills of Nepal: Do socio‐economic factors matter for sustainable land use?. (28th July 2020) - Karna, Romy Das; Bauer, Siegfried
Abstract: Soil nutrient balance studies have become increasingly influential in policy discussions about soil fertility management and sustainable agriculture in developing countries. However, such studies, particularly in the context of Nepal, have often overlooked socio‐economic characteristics of farm households that may have a significant influence upon soil nutrient balances. This study, therefore, estimates the balances of three macronutrients—nitrogen (N), phosphorus (P), and potassium (K)—and analyzes the impact of socio‐economic factors on each of them applying a Seemingly Unrelated Regression (SUR) model. The results indicate that farm households in the study area had an average annual surplus of 31 ± 73 kg ha −1 N but an annual deficit of 20 ± 53 kg ha −1 P and 45 ± 64 kg ha −1 K. Socio‐economic variables, such as distance to the market center, distance to plot from the homestead, possession of sloping farming plots, and having received training on nutrient management showed a negative impact on the nutrient balances. In contrast, male‐headed households, family size, and the use of improved composting methods showed a positive impact on nutrient balances. The study suggests that increased supply of organic sources of P and K via improved composting, better accessibility to inorganic P and K fertilizer through improved marketing infrastructure, and site‐specific fertilizer recommendations more accountable to the changing pattern of cultivation in mid‐hill region may contribute to reducing the trend of nutrient mining. Further, gender‐sensitive extension services are needed to provide female‐headed households with better knowledge and skills to manage their soil nutrients.